The implementation features of the personnel policy principles in public administration - Ataniyazov, Zh.; Tasmaganbetov, A.B. (BUKETOV BUSINESS REVIEW, 2024)
The article deals with the basics of personnel policy in the public administration, which is focused on ensuring high efficiency, competence and integrity of public authorities. The authors highlighted the main methods of increasing the efficiency of labor: the reorganization of the labor process; changes to standards; training, improvement of professional skills; improvement of incentive programs; the backward movement of employees to other positions; the dismissal and recruitment of new teams. The article describes the basic principles of public service in the Republic of Kazakhstan, which serve as a good basis for the development of specific concepts and mechanisms of human resources policy. The authors define the principles of personnel policy, through which the selection of qualified personnel, their professional development and gradual career advancement in the Republic of Kazakhstan. The article groups the existing different interpretations of the principles of personnel policy in public administration. Special attention is paid to the special and universal principles of personnel policy in public administration, which determine all personnel relations and processes. The article reveals the main reasons for the ineffective implementation of the principles of personnel policy in the activities of public administration. The authors recommend specific areas of integrated use of the principles of personnel policy in public administration.